DAKWAH DAN PEMBERDAYAAN MASYARAKAT PERDESAAN - Ahmad Zaini (Jurnal Ilmu Dakwah, 2017)
This paper aims to determine the activities of da'wah in changing the economic, social, cultural, educational and political conditions of rural residents through community empowerment in the frame of da'wah . Namely da'wah that can improve the quality of faith as well as the quality of life target da'wah . The results of this literature review indicate that there are several forms to empower communities through political, economic, socio-cultural and environmental empowerment. The techniques for improving the situation can be done through non-participation techniques, tokenism techniques, and community participation/power techniques. The participation in government, preachers, community, and da'wah organizations in bridging the mission of community empowerment is an urgent thing to be synergized so that the goal of da'wah can succeed maximally